2021
DOI: 10.3389/fmolb.2021.805625
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines and Chemokines in HBV Infection

Abstract: Chronic hepatitis B virus (HBV) infection remains a leading cause of hepatic inflammation and damage. The pathogenesis of chronic hepatitis B (CHB) infection is predominantly mediated by persistent intrahepatic immunopathology. With the characterization of unique anatomical and immunological structure, the liver is also deemed an immunological organ, which gives rise to massive cytokines and chemokines under pathogenesis conditions, having significant implications for the progression of HBV infection. The intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 177 publications
2
27
0
Order By: Relevance
“…These findings implied that chronic HBV infection resulted in the host’s immune disorder and dysregulation by upregulating immune checkpoint molecules, including TIM-3, PD-1, CTLA-4, and LAG-3 on T cells, that induced T-cell dysfunction in chronic HBV infection. In addition, our results showed that serum cytokines (IL-2, IL-4, and TNF-a) had a low trend in chronic ASCs with HBeAg-negative in comparison with HC, which were partially consistent with previous reports ( Ayada et al, 2006 ; Wang X. et al, 2018 ; Zhong et al, 2021 ). These cytokines play a critical role in regulating CD4/CD8 + T cell proliferation and differentiation and the production of various specific antibodies to control persistent HBV infection ( Buschow and Jansen, 2021 ; Mak et al, 2021 ; Zhong et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings implied that chronic HBV infection resulted in the host’s immune disorder and dysregulation by upregulating immune checkpoint molecules, including TIM-3, PD-1, CTLA-4, and LAG-3 on T cells, that induced T-cell dysfunction in chronic HBV infection. In addition, our results showed that serum cytokines (IL-2, IL-4, and TNF-a) had a low trend in chronic ASCs with HBeAg-negative in comparison with HC, which were partially consistent with previous reports ( Ayada et al, 2006 ; Wang X. et al, 2018 ; Zhong et al, 2021 ). These cytokines play a critical role in regulating CD4/CD8 + T cell proliferation and differentiation and the production of various specific antibodies to control persistent HBV infection ( Buschow and Jansen, 2021 ; Mak et al, 2021 ; Zhong et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, our results showed that serum cytokines (IL-2, IL-4, and TNF-a) had a low trend in chronic ASCs with HBeAg-negative in comparison with HC, which were partially consistent with previous reports ( Ayada et al, 2006 ; Wang X. et al, 2018 ; Zhong et al, 2021 ). These cytokines play a critical role in regulating CD4/CD8 + T cell proliferation and differentiation and the production of various specific antibodies to control persistent HBV infection ( Buschow and Jansen, 2021 ; Mak et al, 2021 ; Zhong et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, IL-6 inhibits HBV transcription by epigenetic mechanisms, in addition to performing a broad range of pro-and anti-inflammatory signaling (36). This pro-inflammatory cytokine pattern is similar to that resulted after the viral infection or TLR-9 stimulation, suggesting a crosstalk between that innate and adaptive immunity influencing the antigen specific immune response (34,67). Clearly, further research involving more relevant animal models is needed to understand the true benefit of a particular Tcell activation pattern.…”
Section: Discussionmentioning
confidence: 92%
“…Clearly, further research involving more relevant animal models is needed to understand the true benefit of a particular Tcell activation pattern. This will ultimately depend on the fine balance between the capacity of the complex cytokine-mediated pathways to boost anti-HBV immunity on one hand, and to potentially cause liver inflammation, on the other (34). An important finding emerging from this study is the equivalence of the S and S/preS1 antigens produced in mammalian cells in terms of activating an efficient WT HBVneutralizing humoral immune response and the evident superiority of the latter immunogen to prevent infection with the G145R vaccine-escape mutant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation